Geotechnical Frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard J. (American Society of Civil Engineers, 2017)
Selected papers from Geotechnical Frontiers 2017, held in Orlando, Florida, March 12-15, 2017. Sponsored by the Industrial Fabrics Association International and the Geo-Institute of ASCE. This Geotechnical Special Publication contains 70 peer-reviewed papers on the geotechnical aspects of transportation systems. Topics include: column-supported embankments; field construction QA and QC; load distribution on buried structures; ground improvement; modeling of pavement variability; roadway materials, modeling, and testing; sinkhole engineering; tunneling methods, modeling, and effects; and site investigations and characterization. GSP 277 will be of interest to geotechnical engineers and researchers working in the transportation industry.
Keywords: Road materials -- Congresses.; Soil mechanics -- Congresses.; Pavements, Flexible -- Design and construction -- Congresses.; Building sites -- Evaluation -- Congresses.; elektronické knihy; electronic books